Efek Bauran Promosi terhadap Keputusan Pembelian Pada PT Haji Kalla Cabang Parepare - Beddu, Megawati; Teri, Teri; Apriyandi, Apriyandi; Sapri, Supriadi; Kamariah, Kamariah (Pascasarjana STIE Amkop Makassar, 2024)
The aim of this research is to find out how the promotion mix influences purchasing decisions at PT. Hadji Kalla, Parepare Branch.This research uses quantitative research. and qualitative with a non-probability sampling technique with the incidental sampling technique used using multiple linear regression. Statistical Package for the Social Sciences (SPSS) application program version 29.1. The total sample was 50 customers.The results of the research show that partially the Promotion Mix has a positive influence and significant with a beta coefficient of 0.169 and a probability of 0.001 (p < 0.05), which means that if the promotion mix is better or better, the stronger the purchasing decision, while simultaneously the promotion mix (advertising, individual sales, sales promotion, and publicity) has a significant and positive effect on value significant of 0.001 (p <0.05).keyword_(1) Promotion Mix, (2)Purchasing Decisions.